139k views
2 votes
The first step in determining the solution to the system of equations, y = -x2 - 4x - 3 and y = 2x + 5, algebraically is to set the

two equations equal as X? - 4x - 3 = 2x + 5. What is the next step?
Set y = 0in y = -x? - 4x - 3.
Factor each side of the equation.
Use substitution to create a one-variable equation.
Combine like terms onto one side of the equation

2 Answers

6 votes

Answer:

Combine like terms onto one side of the equation

is the answer , just got it right on edg 2020

Explanation:

User John Dugan
by
4.8k points
1 vote

Answer:

Combine like terms onto one side of the equation

Explanation:

You have

-x^2 -4x - 3 = 2x + 5

It seems that we should combine like terms to make this equations smaller.

-x^2 - 4x - 3 - 2x - 5 = 0

-x^2 -6x - 8 = 0

- (x + 2)(x + 4) = 0

x = -2 or x = -4

User Fadly Dzil
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.